2020
DOI: 10.1155/2020/8850309
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Structural and Microvascular Alterations in Different Acute Ischemic Stroke Subtypes

Abstract: Introduction. Retinal structural and microvascular damages reflect damage to cerebral microvasculature and neurons. We aimed to investigate neovascular unit abnormalities among patients with large-artery atherosclerosis (LAA) or small-vessel occlusion (SAA) and control subjects. Methods. Twenty-eight LAA patients, forty-one SAA patients, and sixty-five age- and gender-matched controls were recruited. Based on optical coherence tomography angiography (OCTA), retinal capillary vessel density was assessed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…It is suggested that the retina can act as a novel and non-invasive imaging marker with potential diagnostic and clinical significance in neurological diseases ( Cabrera DeBuc et al, 2017 ; Mutlu et al, 2017 ; Kwapong et al, 2018 ). Thinning of the retinal nerve fiber layer (RNFL) and ganglion cell layer (GCL)-inner plexiform layer (GCIPL) has been consistently documented in previous reports ( Park et al, 2013 ; Zhang et al, 2020 ; Kashani et al, 2021 ; Snyder et al, 2021 ; Ye et al, 2022 ) in most cerebrovascular disorders. These reports suggest retinal neurodegeneration reflects cerebral neurodegeneration, and this mechanism may occur simultaneously.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…It is suggested that the retina can act as a novel and non-invasive imaging marker with potential diagnostic and clinical significance in neurological diseases ( Cabrera DeBuc et al, 2017 ; Mutlu et al, 2017 ; Kwapong et al, 2018 ). Thinning of the retinal nerve fiber layer (RNFL) and ganglion cell layer (GCL)-inner plexiform layer (GCIPL) has been consistently documented in previous reports ( Park et al, 2013 ; Zhang et al, 2020 ; Kashani et al, 2021 ; Snyder et al, 2021 ; Ye et al, 2022 ) in most cerebrovascular disorders. These reports suggest retinal neurodegeneration reflects cerebral neurodegeneration, and this mechanism may occur simultaneously.…”
Section: Introductionmentioning
confidence: 56%
“…The last few decades have seen a substantial increase in research identifying alterations in retinal structure and microvasculature after stroke ( Park et al, 2013 ; Wang et al, 2014 ; Zhang et al, 2020 ; Kwapong et al, 2021 ). It is suggested that the retina can act as a novel and non-invasive imaging marker with potential diagnostic and clinical significance in neurological diseases ( Cabrera DeBuc et al, 2017 ; Mutlu et al, 2017 ; Kwapong et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…They have the same embryo origin and histological structure as cerebral vessels ( 10 13 ). Retinal microvascular damages can reflect damage to cerebral microvasculature and neurons ( 14 ). It provides us with a convenient way to assess cardiovascular conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in vessel density in the deep retinal plexus was not significant. A study on retinal structural and microvascular alterations in individuals with acute ischaemic stroke of various subtypes noted reduced vessel density, and the deep microvascular network was more sensitive to ischaemic stroke than was the superficial microvascular network [ 31 ]. However, another study displayed that decreased vessel density of the superficial retinal plexus could be a biomarker of SVD [ 32 ].…”
Section: Discussionmentioning
confidence: 99%